P020 The impact of COVID-19: local observations from the National Early Inflammatory Arthritis Audit. (23rd April 2022) - MacPhie, Elizabeth; Ashcroft, Lesley; Foreman, Nicola; GIlbert, Sharon; Horton, Sarah; Madan, Ayesha; Moon, Kirsty; Rao, Chandini; Fish, Sarah
Abstract: Background/Aims: The National Early Inflammatory Arthritis Audit (NEIAA) has provided the opportunity for rheumatology services to benchmark the care they provide against NICE quality standards (QS)33. It has proven to be a powerful lever for improving quality and our department is testimony to this. Recruitment to all national audits was paused for several months due to the COVID-19 pandemic. Once pressures had eased we recognised that NEIAA would help to understand the impact of the pandemic on the diagnosis and initial management of patients with rheumatoid arthritis. Our department continued to see all new urgent referrals face-to-face and were fortunate that the team were not redeployed. Methods: Data submitted to the NEIAA online tool during year 3 (September 2020-March 2021) were downloaded for analysis. Data from year 2 were downloaded for comparison. Results: In year 3, 154 patients were recruited to the audit compared to 268 in year 2. 36 (23%) had rheumatoid arthritis and were included in the follow-up cohort compared to 73 (27%) in year 2. All patients had a baseline and a 3-month follow up form completed, however 17 patients in year 3 had a telephone appointment at 3 months and there was no available DAS28. Patient demographics were similar. The case mix of patients recruited was also; in year 3, 41% were diagnosed with autoimmune inflammatory arthritis compared to 47% in year 2 and 42% with a non-inflammatory condition compared to 39% in year 2. In year 3, 41% of all patients were seen within 3 weeks of being referred and 58% of patients with RA started DMARD therapy within 6 weeks of referral. This compared to 54% and 56%, respectively, in year 2. In year 3, symptom duration prior to referral appeared longer: 31% had symptoms for less than 3 months, 31% for 3-6 months, 22% for 6-12 months and 16% for more than 12 months compared to 67%, 18%, 12% and 3%, respectively, in year 2. DAS28 at baseline was higher in year 3 with 47% high, 47% moderate and 6% low disease activity or in remission compared to 27%, 61% and 12%, respectively, in year 2. DAS28 at 3-months was also higher in year 3 with 16% high, 37% moderate and 27% low disease activity or remission compared to 6%, 25% and 69% respectively in year 2. Conclusion: Despite the impact of the pandemic we have maintained our performance against QS2 and 3. However, patients seemed to have longer duration of symptoms prior to referral, higher disease activity at baseline and at 3 months. We await the 12-month data to determine 1-year outcomes, including escalation to high cost drug therapies. Disclosure: E. MacPhie: Other; EM is the secretary of the North West Rheumatology Club, meetings have been supported by UCB, MSD, Abbvie and Lilly. L. Ashcroft: None. N. Foreman: None. S. GIlbert: None. S. Horton: None. A. Madan: None. K. Moon: None. C. Rao: None. S. Fish: None.